Patient perspectives on patient similarity-based risk communication for uncontrolled type 2 diabetes in primary care: A qualitative study. - Ruiheng Ong; Chirk Jenn Ng; Kalaipriya Gunasekaran; Hang Liu; Wynne Hsu; Mong Li Lee; Ngiap Chuan Tan (PLoS ONE)
Background The inertia to adopt protective health behaviours by patients with diabetes is contributed by underestimation of their risks of diabetes complications. Risk communication, using social comparison of glycaemic control and disease trajectory to other patients of similar clinicodemographic profiles, has potential to increase patients' risk perceptions and motivate protective health behaviours. A digital tool named PERDICT.AI was designed to support primary care physicians (PCPs) in patient similarity-based risk communication to patients with type 2 diabetes mellitus (T2DM). Aim This study explored the perspectives of patients with uncontrolled T2DM on how their diabetes-related risks were communicated to them by a PCP using PERDICT.AI. Methodology A qualitative design was used. Eighteen participants aged 40-79 with T2DM with ≥1 HBA1c reading ≥8.0% within the last 6 months were recruited from a primary care clinic in Singapore. Each participant went through the risk communication session followed by an in-depth interview. The transcripts were coded and analysed to identify emerging themes. Results Five themes emerged representing participants' risk perceptions post-session and social comparison tendencies. These are: 1) 'I am myself', 2) motivation to be like the majority, 3) avoiding similar negative outcomes, 4) low risk does not equate to zero risk, and 5) motivation to replicate how others achieve positive outcomes. Themes 1 and 4 were concurrently represented among some participants; zero risk tolerance for diabetes complications was expressed despite not being motivated by their HBA1c cohort ranking. Conclusion This study provided insights into the acceptability of using a social comparison approach in communicating risk to patients with uncontrolled T2DM. It highlights the importance of identifying and selecting patients who are receptive to social comparison, clarifying patients' perceptions of risks, including zero risk, and providing tailored and socially comparable strategies to mitigate these risks.